STUDY REGARDING USING SOLAR ENERGY FOR HOUSEHOLD`S SUFFICIENCY AND RURAL COMMUNITIES DEVELOPMENT IN UKRAINE - Inna LOZYNSKA; Olena SKRYPNYK; Denys SKRYPNYK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The recent statistical data and market studies have shown that today Ukraine electricity market requires certain changes and modifications. Reform is necessary to build a new model of interaction between all participants in the energy market. The problem is too monopolized the electricity market, lack of understanding of the marketability of the category, transparency of electricity pricing, the ability to freely choose contractors and so on. Therefore, we can safely say that the new model of the energy market of Ukraine should be a powerful impetus to the energy sector development, which will lead to key indicators of sustainable economic development - energy efficiency, energy sufficiency, energy independent, use of renewable resources. This study surveyed households using solar photovoltaics to determine the prospects for solar energy in rural communities. Like methodology of research options for the development of alternative energy households, were considered traditional, technical and economic factors such as technological readiness and ability to pay, access to information and experience, if you want to implement sustainable energy solutions in rural communities. Were also identified factors that influence the household's decision to install a photovoltaic module. The survey asked about the demographic data of the respondent (gender, age and level of education) and household (household size, type of business and income) to find out their level of electricity needs. These findings indicate that the positive experience of rural users undoubtedly offers business opportunities to interact with rural households in meeting the unmet energy needs for further market growth.